2016
DOI: 10.1021/acssuschemeng.5b01627
|View full text |Cite
|
Sign up to set email alerts
|

RuO2·nH2O Nanoparticles Anchored on Carbon Nano-onions: An Efficient Electrode for Solid State Flexible Electrochemical Supercapacitor

Abstract: A flexible solid state electrochemical capacitor based on hydrous RuO2 nanoparticles, supported onto the nonporous and highly accessible ion adsorptive carbon nano-onions (CNOs), is fabricated in a novel process of modifying a conducting carbon paper to a flexible conducting substrate, separated with a poly­(vinyl alcohol)/H2SO4 gel electrolyte. The sol–gel technique tends to form homogeneously dispersed RuO2 nanoparticles with the average size of ∼2.3 nm on the positive surface curvatures of multilayer fuller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 26 publications
2
56
0
Order By: Relevance
“…Figure S7c (Supporting Information) shows a typical Ru3p 1/2 peak at 485 eV and Ru3p 3/2 peak at 462.5 eV from RuO 2 . The Ru3p 3/2 peak can be deconvoluted into two peaks at 462.3 eV from RuO 2 and 464.0 eV from Ru(OH) 2 . Overall, the XPS results suggest that nano‐RuO 2 particles formed in the fibers are in hydrated form (RuO 2 · x H 2 O), which is beneficial for charge storage and ionic transport …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure S7c (Supporting Information) shows a typical Ru3p 1/2 peak at 485 eV and Ru3p 3/2 peak at 462.5 eV from RuO 2 . The Ru3p 3/2 peak can be deconvoluted into two peaks at 462.3 eV from RuO 2 and 464.0 eV from Ru(OH) 2 . Overall, the XPS results suggest that nano‐RuO 2 particles formed in the fibers are in hydrated form (RuO 2 · x H 2 O), which is beneficial for charge storage and ionic transport …”
Section: Resultsmentioning
confidence: 92%
“…And importantly, no crystalline diffraction peaks from RuO 2 (e.g., JCPDS file 40‐1290) were observed, even though the mass loading is high, which suggests that amorphous RuO 2 was formed in the fiber. Previous studies have reported that amorphous RuO 2 possesses higher capacitance than its crystalline structure …”
Section: Resultsmentioning
confidence: 95%
“…The obtained monolith was taken and washed thoroughly with distilled water before using it further. Of note, it is important to maintain the right ratio of Ni(OH) 2 and GS for being used as a good supercapacitor electrode since the capacitance is different for each of the individual constituents, the GS contributing much less toward the overall capacitance. In this study, two samples with graphene contents of 16.5% and 24.9% were prepared.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
“…1,2 In comparison with the widely used and common double-layer capacitors, pseudocapacitors (for example, metal oxide, metal hydroxide, and polymers) have higher specific capacitance, as a result of which they are widely explored and considered for supercapacitor applications. 3−5 But, the use of these materials has been disadvantaged by their low cyclic stability and rate capability, due to the low conductivity of these materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…are still being extensively investigated at present. As typical electrode active species, RuO 2 is the most promising pseudocapacitive electrode material among the transition metals with remarkably high specific capacitance, high chemical and thermal stability, and good electrochemical redox properties, then their hybrid such as RuO 2 /reduced grapheme [33], RuO 2 ·nH 2 O/carbon nano-onions [34], RuO 2 /CNFs [35], etc. are also developed to get reasonable structure and improve their performance.…”
Section: Carbon-based Materials For Pseudocapacitorsmentioning
confidence: 99%